Analisis Aspek Risiko Produk Gadai Emas pada PT Pegadaian Syariah Cabang Medan Petisah - Devita, Devita; Zainarti, Zainarti (Jurnal Ekonomi Manajemen Perbankan, 2025)
This study aims to analyze the risk aspects associated with gold pawn products at PT. Pegadaian Syariah Medan Petisah Branch. These risks include counterfeit gold, collateral damage, fluctuating gold prices, and operational risks in appraisal and storage processes. The research method employs a qualitative approach using data collection techniques such as in-depth interviews, observation, and document studies. The findings reveal that PT. Pegadaian Syariah has implemented risk management practices, including modern tools for verifying gold quality, training for appraisers, and multi-layered storage systems to ensure collateral security. However, the fluctuating gold price risk remains a major challenge as it can impact the company's profit margins and customers' ability to redeem their collateral. This study suggests strengthening hedging policies and product diversification to mitigate the effects of gold price fluctuations.